Direct writing of single germanium vacancy center arrays in diamond. (14th December 2018) - Zhou, Yu; Mu, Zhao; Adamo, Giorgio; Bauerdick, Sven; Rudzinski, Axel; Aharonovich, Igor; Gao, Wei-bo
Abstract: Color centers in diamond are promising solid-state qubits for scalable quantum photonics applications. Amongst many defects, those with inversion symmetry are of an interest due to their promising optical properties. In this work, we demonstrate a maskless implantation of an array of bright, single germanium vacancy (GeV) centers in diamond. Employing the direct focused ion beam technique, single GeV emitters are engineered with the spatial accuracy of tens of nanometers. The single GeV creation ratio reaches as high as 53% with the dose of 200 Ge + ions per spot. The presented fabrication method is promising for future nanofabrication of integrated photonic structures with GeV emitters as a leading platform for spin-spin interactions.